2011
DOI: 10.1016/j.jep.2011.09.047
|View full text |Cite
|
Sign up to set email alerts
|

Witoto ash salts from the Amazon

Abstract: There is a correlation between the concentration of the three anions and the perceived taste of the salts, the "sweet" flavor of chloride being the preferred taste. Our research shows that the culinary function of these salts is secondary to their ritual, medicinal and cosmological meaning. The search for chloride is one of the reasons to produce and consume these salts; other reasons are also important: their alkaline pH, which liberates the alkaloid of the tobacco with which the salts are mixed; and their co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 10 publications
3
17
0
Order By: Relevance
“…From the present study, it is very clear that some of the s-, d-and p-block elements (Li, Na, Mg, Ca, Sr, Ba, V, Mo, Mn, Fe, Cu, Zn and B) are present in low concentrations (<0.001%-1.341%) while potassium is the most common and present in abundance (21.64%-45.02%). The same was also reported [12] and the values are <0.001%-0.630% and 27.00%-48.50% respectively for almost all the salts obtained from various plant species belonging to different families.…”
Section: Why Only Certain Plants and Why Not Others?supporting
confidence: 74%
See 4 more Smart Citations
“…From the present study, it is very clear that some of the s-, d-and p-block elements (Li, Na, Mg, Ca, Sr, Ba, V, Mo, Mn, Fe, Cu, Zn and B) are present in low concentrations (<0.001%-1.341%) while potassium is the most common and present in abundance (21.64%-45.02%). The same was also reported [12] and the values are <0.001%-0.630% and 27.00%-48.50% respectively for almost all the salts obtained from various plant species belonging to different families.…”
Section: Why Only Certain Plants and Why Not Others?supporting
confidence: 74%
“…Based on the limited reports available [11,12,14,16,27], common cations present in various Comparison of the minerals content on the basis of average daily intake (~10 g) and the RDI (mg/d). [17] on rats indicated that the salts, when used in suitable quantity contain enough NaCl for the physiological needs in higher animals and humans in spite of containing large amounts of potassium ions.…”
Section: Cationic and Anionic Constituentsmentioning
confidence: 99%
See 3 more Smart Citations